The effects of promoting oral intake using the Kuchi-kara Taberu index, a comprehensive feeding assistant tool, in older pneumonia patients: a cluster randomized controlled trial - Shamoto, Hiroshi; Koyama, Tamami; Momosaki, Ryo; Maeda, Keisuke; Wakabayashi, Hidetaka (BMC geriatrics, 2020)
The multidisciplinary comprehensive care (MDCC) program promotes the improvement of oral intake for older patients. The Kuchi-kara Taberu (ingesting orally in Japanese, KT) index was developed to objectively assess patient conditions in the MDCC program. This trial examined the effects of the index in promoting oral intake in older patients with pneumonia. A cluster randomized controlled trial was conducted in 10 local hospitals targeting older patients with pneumonia (≥65 years). Ten hospitals were allocated randomly to either the intervention or the control group. Both groups (each with five hospitals) received the MDCC program for oral feeding, which consisted of professional assessment, care, and treatment. The KT index was used by the intervention group, focusing on improving low score items. The primary outcome was determined using the Functional Oral Intake Scale (FOIS) at discharge or 1 month after admission. One hundred and twelve patients (46 women and 66 men) who participated from 10 hospitals, with a median age of 88 years (interquartile range [IQR], 80-91), were examined. The median FOIS level and the number of patients with oral intake (FOIS ≥ level 4) at discharge were 4 (IQR, 4-6) and 89 (79.5%), respectively. The duration of nil per os was 2 (IQR, 1-5) days. Clusters were not matched in the presence of Kuchi-kara Taberu Shiawase-wo Mamoru-kai-certified medical staff promoting oral intake in patients with dysphagia in each hospital. The median FOIS levels of 53 patients in the intervention group and 59 patients in the control group were 5 (IQR, 4-6) and 4 (IQR, 4-5), respectively, showing no statistically significant difference (P = 0.76). According to a multivariate analysis, the KT index had no positive effect on FOIS levels. This trial was not able to demonstrate the usefulness of the KT index due to random assignment failure. However, both the intervention and control groups showed a high prevalence of oral intake (FOIS ≥ level 4) at discharge. UMIN-Clinical Trial Registry, UMIN000025172, December 17, 2016.